Drinking water contamination by heavy metals in different cities of Pakistan - Hussain, Shabbir; Amjad, Muhammad; Ambreen, Hina; Batool, Iqra (International Journal of Advanced Chemistry, 2021)
The most important concern in developing countries like Pakistan is the contamination of groundwater because of the heavy metals from industrial waste which are affecting the ecosystem and public health. Some heavy metals such as Arsenic (As), Chromium (Cr), Nickel (Ni), Copper (Cu), Iron (Fe), Lead (Pb) and Zinc (Zn) are mostly reported in different cities of Pakistan and their concentrations are also to be found above the permissible levels of WHO. For domestic purposes and irrigation, groundwater is the main source in Pakistan. Its quality is getting poor because of the untreated discharge from industries. In the country, water-borne diseases are spreading quickly because of the use of unfiltered environmentally contaminated water as well as a lack of awareness of environmental laws.Â Â